Dosimetric and radiation cancer risk evaluation of high resolution thorax CT during COVID-19 outbreak. (December 2020) - Ghetti, C.; Ortenzia, O.; Maddalo, M.; Altabella, L.; Sverzellati, N.
Highlights: A large number of high resolutions thorax CT scans collected for suspected SARS-CoV-2 infection. The use of an advanced software guarantees a great accuracy to calculate organ doses and effective doses. Monitoring in real time all the dosimetric aspects of COVID-19 outbreak. Cancer risk estimation according to the BEIR VII. Abstract: Purpose: The aim of this work was to evaluate the dosimetric impact of high-resolution thorax CT during COVID-19 outbreak in the University Hospital of Parma. In two months we have performed a huge number of thorax CT scans collecting effective and equivalent organ doses and evaluating also the lifetime attributable risk (LAR) of lung and other major cancers. Materials and Method: From February 24th to April 28th, 3224 high-resolution thorax CT were acquired. For all patients we have examined the volumetric computed tomography dose index (CTDIvol), the dose length product (DLP), the size-specific dose estimate (SSDE) and effective dose (E103 ) using a dose tracking software (Radimetrics Bayer HealthCare). From the equivalent dose to organs for each patient, LAR for lung and major cancers were estimated following the method proposed in BEIR VII which considers age and sex differences. Results: Study population included 3224 patients, 1843 male and 1381 female, with an average age of 67 years. The average CTDIvol, SSDE and DLP, and E103 were 6.8 mGy, 8.7 mGy, 239 mGy· cm and 4.4 mSv respectively. The average LAR of all solid cancers was 2.1 cases per 10, 000 patients, while the average LAR of leukemia was 0.2 cases per 10, 000 patients. For both male and female the organ with a major cancer risk was lung. Conclusions: Despite the impressive increment in thoracic CT examinations due to COVID-19 outbreak, the high resolution low dose protocol used in our hospital guaranteed low doses and very low risk estimation in terms of LAR.